Hydroformylation of Unsaturated Dicarboxylic Esters with Rhodium Containing Catalysts - László Kollár; Giambattista Consiglio; Piero Pino (CHIMIA)
The regioselectivity observed in carbonyl-rhodium catalyzed hydroformylation of dimethyl itaconate (1a), which leads to the preferential formation of dimethyl 2-(formylmethyl)-butandioate (3a) is completely reversed by the modification of the catalyst with phosphanes resulting in the formation of dimethyl 2-formyl-2-methyl-butandioate (2a). Only the hydrogenation reaction was observed under «oxo» conditions for the isomeric dimethyl mesaconate (1b) or dimethyl citraconate (1c). A low enantioface discrimination involving the same face both for hydrogenation and hydroformylation is found in the reaction of 1a using the chiral ligand (R,R)-2,2-dimethyl-4,5-(diphenylphosphinomethyl)-1,3-dioxolane (DIOP).